Chapter Il lavoro e l’Intelligenza Artificiale generativa - Mari, Giovanni (Firenze University Press, 2025)
The transfer into the machine first of the manual skills and then of the worker's thoughts has determined an unprecedented condition for the production activity which must be analyzed according to the purposes of the individual jobs. In general, it should be underlined that the combined automation plus AI tends to replace repetitive jobs, but that AI thinking is characterized by being "blind" (Leibniz), that is, devoid of a representation of consciousness, and therefore linked to the statistical processing of data already prepared. Which, despite possessing a computing power extraordinarily superior to that of human thought, lacks the degree of creativity of the latter. Unreplaced work can therefore find in AI a collaboration tool in which to achieve unprecedented degrees of increased capacity and creativity. For this to happen, a radically renewed organization and concept of production is needed.